1988
DOI: 10.1080/17450398809428309
|View full text |Cite
|
Sign up to set email alerts
|

Profile of isoacids in rumen fluid and influence of added isoacids on in sacco dry matter disappearance of untreated and ammonia treated wheat straw

Abstract: The influence of type of diet and time after feeding on concentration of isoacids in rumen fluid of 6 fistulated sheep were investigated. The concentration of isoacids in rumen fluid was higher in diets rich in concentrate and protein (5.6) than in roughage diets (3.4) or in straw-starch-urea diets poor in native protein (highest concentration: 2.1 mmol/l rumen fluid). Feeding of roughage diet or straw-starch-urea-diet effected a significant decrease of concentration of isoacids in the rumen fluid after mornin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Liu et al digestibility in the present study is in agreement with other studies (Soofi et al 1982;Gorosito et al 1985). Flachowsky et al (1988) reported that a daily infusion of 3 g BCVFA in the rumen of sheep increased in situ DM loss of ammonia treated wheat straw by 8. 1, 11.7, 9.4, 4.3 and 7.1% after 6, 12, 24, 48 and 72 h of ruminal incubation, respectively.…”
Section: In Situ Ruminal Degradability and Apparent Digestibility In supporting
confidence: 95%
“…Liu et al digestibility in the present study is in agreement with other studies (Soofi et al 1982;Gorosito et al 1985). Flachowsky et al (1988) reported that a daily infusion of 3 g BCVFA in the rumen of sheep increased in situ DM loss of ammonia treated wheat straw by 8. 1, 11.7, 9.4, 4.3 and 7.1% after 6, 12, 24, 48 and 72 h of ruminal incubation, respectively.…”
Section: In Situ Ruminal Degradability and Apparent Digestibility In supporting
confidence: 95%
“…() reported that populations of total bacteria, R. albus and F. succinogenes increased with increasing dietary CP level in buffaloes. Similarly, dietary BCVFA supplementation provided essential nutrient for ruminal cellulolytic bacteria and promoted microbial growth (Cummins & Papas, ; Flachowsky et al., ). Previous studies found that populations of R. albus , R. flavefaciens , B. fibrisolvens and F. succinogenes, and activities of carboxymethyl‐cellulase and xylanase increased, but microbial protease activity decreased with isovalerate or isobutyrate supplementation (Liu et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The result confirmed the findings of previous studies that the effects of BCVFA supplementation were associated with dietary CP content and quality (Liu et al., , ; Wang et al., ). Literature demonstrated that ruminal BCVFA derived from the degradation of branched chain amino acids and could provide carbon skeleton for corresponding amino acids synthesis (Cummins & Papas, ; Flachowsky et al., ). Dietary MB supplementation could reduce the degradation of branched chain amino acids, thus the utilization of protein improved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations